Determination of Lycopene Concentration in Fresh Tomatoes by Spectrophotometry: A Collaborative Study. (11th April 2020) - Kakubari, Sachiko; Sakaida, Kenichi; Asano, Masahiro; Aramaki, Yoshinori; Ito, Hidekazu; Yasui, Akemi; Iwamaru, K; Kaneda, T; Kitamura, M; Matsumoto, T; Miyamoto, M; Mizuta, K; et al.
Abstract: Background: Lycopene has been the object of considerable research attention recently, and the effects of the intake of lycopene, or of tomato products, have been studied in various ways. In Japan, interest in the health-promoting function of food components has increased. Objective: Developing a method to determine lycopene contents in tomato that meets the Japanese Agricultural Standard (JAS). Method: In the proposed JAS method, the test sample consists of fresh tomatoes; a hexane–acetone mixture is utilized as the extraction solvent. A collaborative study was conducted to evaluate the interlaboratory performance of the method. Results: Ten laboratories participated and analyzed six test materials characterized by a lycopene content between 39 and 170 mg/kg as blind duplicates. After removing statistical outliers, RSDr ranged from 1.2 to 3.0% and RSDR ranged from 2.4 to 4.2%. The HorRat values were calculated and found to be in the 0.26–0.49 range. Conclusions: The method for determining the lycopene content in tomato was evaluated by means of a collaborative study, and the reproducibility of this method was found to be acceptable. Highlights: Intended for standardization in Japan, a method to determine lycopene content in tomato has been developed and shown to have acceptable precision in a collaborative study.